2021
DOI: 10.3390/math9233101
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Initial Stages of Alzheimer’s Disease through Pet Neuroimaging Modality and Deep Learning: Quantifying the Impact of Image Filtering Approaches

Abstract: Alzheimer’s disease (AD) is a leading health concern affecting the elderly population worldwide. It is defined by amyloid plaques, neurofibrillary tangles, and neuronal loss. Neuroimaging modalities such as positron emission tomography (PET) and magnetic resonance imaging are routinely used in clinical settings to monitor the alterations in the brain during the course of progression of AD. Deep learning techniques such as convolutional neural networks (CNNs) have found numerous applications in healthcare and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Out-of-set generalization had remained a challenge for Computer Vision, which has been resolved with the availability of recurrence and feedforward learning networks. DNNs can be used to find hidden patterns from the data and learn the classification decision boundaries concurrently, thus skipping the tedious step of feature engineering, making them a viable choice for medical imaging modalities [8]. In [9], it was reported that rather than training an entire model from the start, it is better to begin from an already-trained deep neural network and then adjust the last layers for the medical image dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Out-of-set generalization had remained a challenge for Computer Vision, which has been resolved with the availability of recurrence and feedforward learning networks. DNNs can be used to find hidden patterns from the data and learn the classification decision boundaries concurrently, thus skipping the tedious step of feature engineering, making them a viable choice for medical imaging modalities [8]. In [9], it was reported that rather than training an entire model from the start, it is better to begin from an already-trained deep neural network and then adjust the last layers for the medical image dataset.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they may be unable to handle more complicated cases where spine pathologies and curvatures are present. In recent years, deep learning has become a research hotspot in medical image analysis [18] because of its high feature extraction ability [19][20][21][22][23][24]. Deep neural networks (DNNs) often use successful tools as an extractor of high-level features.…”
Section: Introductionmentioning
confidence: 99%
“…Machine and deep learning (ML/DL) techniques have received substantial attention for the assessment of data from different sets of inputs such as text, images or volumes for different applications such as depression recognition [8], opinion leader identification [9], multi-object fuse detection [10], AD classification [11][12][13], cancer prediction [14], joint Alzheimer's and Parkinson's diseases classification [15,16], automatic modulation classification [17,18], diabetic retinopathy classification [19], AD assessment using independent component analysis technique [20], and endangered plant species recognition [21]. These methods can optimally infer representations from raw data through the use of a stratified sampling approach with many varying levels of intricacies.…”
Section: Introductionmentioning
confidence: 99%